Effects of Using Digital Devices on Food Consumption among University Students in Nepal - Joshi, Dirgha Raj; Neupane, Umesh; Singh, Jitendra Kumar; Khanal, Bishnu; Belbase, Shashidhar (International Research Journal of MMC, 2021)
Food consuming behavior is a concern for good physiological, physical, psychological, and social health. An unbalanced eating habit may be related to several factors. The objective of the study was to investigate how the use of digital devices influences graduate students’ eating behavior. A cross-sectional study was conducted among 320 Masters of Philosophy (MPhil) scholars of Nepal Open University through an online survey. A Chi-square test and a binary logistic regression model were fitted to find the effect of digital devices on food consumption. There was a significant association between the duration of using a mobile phone, computer, and TV with the quantity of food consumed, preferred time of using a laptop with the quantity of food consumed, and the sitting position during the use of digital devices with the quantity of food consumed. The logistic regression model showed that individual’s sitting positions while using digital devices were significant predictors of food consumption at a 95% confidence level.